Business Strategy and Corporate Environmental Performance: Evidence from High Environmental Risk Countries in the Asian Region - Hilma Tsani Amanati; Choirunnisa Arifa (The Indonesian Journal of Accounting Research, 2022)
Abstract: This study aims to provide empirical evidence of the effect of business strategy on the management and operational performance of the company's environment. This study examines business strategy as a company's fundamental element in corporate decision making and focuses on prospector and defender business strategies as strategies that are at opposite extremes of the continuum. The research sample is non-financial companies listed on the Indonesia, India and China Stock Exchanges. The final sample in this study consisted of 869 company observations and years, with the research period from 2015 to 2019. Data analysis was carried out by panel data regression using STATA 16 tools. We found that the company's business strategy had a significant effect on environmental management performance and performance. operational environment of the company. Overall, prospector and defender business strategies have different tendencies towards the level of environmental management performance and environmental operational performance. Companies with a prospector business strategy, even though they have a lower level of environmental management performance, are able to maintain their environmental externalities well. Meanwhile, a company with a defender business strategy managerially has a strategic planning system that has been stable but tends to limit involvement in environmental activities in real terms with cost considerations. This research can serve as an illustration for regulators to consider proactive environmental policies for companies. Keywords: business strategy, environmental management performance, environmental operational performance